Chironomidae (Diptera) of Shalmash Falls, West Azerbaijan, Iran, with the description of Paracricotopus davoodi sp. nov., a new Orthocladiinae - Ghaderi, Edris; Ibrahimi, Halil; Mohammadi, Habibollah; Namayandeh, Armin (Zootaxa, 2023)
In this study, we describe Paracricotopus davoodi sp. nov., a new Orthocladiinae, and report on eight new faunistic records from Iran, further extending their distribution within the Palearctic realm. Along with describing a new species, we provide a key for the adult males and immatures of the genus Paracricotopus Brundin, 1956. We conducted this study as part of our ongoing investigation of the Chironomidae biodiversity in western Iran, where we aim to database new faunistic records and new taxa in the freshwaters of the Zagros Mountains. The studied freshwater, Shalmash Falls, is part of the main channel of the Little Zab River tributary that originates from the natural springs and glacier-fed runoffs of the Zagros Mountains. The Shalmash Falls is considered a natural wonder of western Iran and has ecotourism importance.